Transitive Hashing Network for Heterogeneous Multimedia Retrieval - Cao, Zhangjie; Long, Mingsheng; Wang, Jianmin; Yang, Qiang (Proceedings of the AAAI Conference on Artificial Intelligence, 2017)
Hashing is widely applied to large-scale multimedia retrieval due to the storage and retrieval efficiency. Cross-modal hashing enables efficient retrieval of one modality from database relevant to a query of another modality. Existing work on cross-modal hashing assumes that heterogeneous relationship across modalities is available for learning to hash. This paper relaxes this strict assumption by only requiring heterogeneous relationship in some auxiliary dataset different from the query or database domain. We design a novel hybrid deep architecture, transitive hashing network (THN), to jointly learn cross-modal correlation from the auxiliary dataset, and align the data distributions of the auxiliary dataset with that of the query or database domain, which generates compact transitive hash codes for efficient cross-modal retrieval. Comprehensive empirical evidence validates that the proposed THN approach yields state of the art retrieval performance on standard multimedia benchmarks, i.e. NUS-WIDE and ImageNet-YahooQA.